REPAIR STRATEGIES IN ONLINE CHAT: Conversation Analysis - Ari Tiara, - (2018)
This research is a conversation analysis which focuses on the analysis of repair in online chat. By using qualitative approach, this study aims to: (1) investigate the types of repair strategies, (2) identify the techniques of repair initiation, and (3) discover the possible functions of particular types of repair employed by the participants of the group conversation namely Calterone 33. The theory of repair strategies from Schegloff, Sacks and Jefferson (1977), and techniques of repair initiation from Finegan (2008) were applied to analyse the data. The results of the present study reveal that the participants in Calterone 33 used all types of repair strategies in which other-initiated self-repair appears as the most frequently occurs (52.5%). It was affected by the topic selection from the participants with different knowledge which triggered the recipient to initiate a repair. Three techniques of repair from Finegan (2008) were found in group's chat room, with an asking question technique as the most applied. It was used as the participants urge the explanation of the trouble source from the current speaker. Another technique was discovered in the chat, namely giving possible understanding. Repair strategies were used in online chat for some functions such as to get a further explanation, to clarify a thing, and to rectify the mistyping in the utterance. This study contradicts Zaferanieh (2004) and Meredith and Stokoe (2013) for its claim that SISR appears as the most applied in online chat; nevertheless, it supports Schonfeldt and Golato (2003), Sato (2012), Kendrick's (2015) study about the use of SISR and other-initiation in conversation. Those findings indicate that the participants in Calterone 33 tend to initiate repair from others' mistakes which are affected by different understanding of the topic. They use other-initiation in order to get an explanation of the trouble source.